Testing the Effectiveness of Kepok Banana (Musa paradisiaca L) Skin Extract on Reducing Blood Sugar Levels in Male Mice (Musmusculus) - Jayanti, Nur (Central Research Institute For Agriculture, 2023)
One natural ingredient that has the potential to be used as traditional medicine is the peel of the Kepok banana (Musa paradisiaca L). This study aims to determine the effect of administering Kepok banana peel extract with different solvents on reducing blood sugar levels in male mice and to determine the secondary metabolite content of Kepok banana peel. This research uses extraction methods, effectiveness testing, fractionation and identification. The effectiveness test was carried out using male mice. Data analysis was carried out by ANOVA using SPSS V 20 for Windows 10 and the Least Significant Difference (BNT) test. Fractionation was carried out using TLC and KKCV. Identification of secondary metabolite compounds was carried out using phytochemical tests and Gas Chromatography Mass Spectrometer (GC-MS). The results of the study showed that the extract that had the greatest effect on lowering blood sugar levels was the ethyl acetate extract of Kepok banana peel which was predicted to contain flavonoid secondary metabolite compounds in the form of flavonoids 5, 7, 3', 5'-tetrahydroxy-3-4-flavon- diol (m/z 306 g/mol).